Effect of tropical peat swamp forest clearing on soil carbon storage - Mat Nuri, Ahmad Shukri; Gandaseca, Seca; Ahmed, Osumanu Haruna; Nik Ab. Majid, Nik Muhamad (Science Publications, 2011)
Problem Statement: Forest clearing in Tropical Peat Swamp Forest (TPSF) will affect forest soil carbon storage. Thus this study is essential to determine whether the effect of clearing of forest does to the nature of soil forest concentrating on soil carbon storage. The objectives of this study were to analyze carbon storage values in logged and clear cut TPSF and to compare these values to see whether clearing of forest will affect its soil in terms of carbon storage. Approach: Soil sampling was conducted in July 2009 on two different plots at Batang Igan, Sibu, Sarawak, Malaysia. The plots are secondary TPSF where this area has been logged but not been cleared while another plot is the clear cut area where the forest has been cut down and cleared for other land use. Soil samples were taken in each plot in the depth of 0-15 cm. Every sample was taken randomly by peat auger using bulking method. The soils were air dried, pounded using mortar and sieved. The bulk densities were determined by coring method. Total Carbon (TC), total Organic Matter (OM), Total Nitrogen (TN) and stable C estimation per hectare were determined from bulk density. The soil pH was determined using pH meter by using water and KCl. SOM, TC and stable C in Humic Acid (HA) were determined by loss-on ignition method. TN was determined using Micro-Kjeldahl method followed by steam distillation and titration. HA was extracted and purified using distilled water. Then, the HA were oven dried in 40oC. The E4/E6 ratio by using spectrometer was used. Total acidity of HA which consists of carboxylic (-COOH) and phenolic (-OH) functional group were analyzed. The statistical analysis and comparison was using t-test to compare between two means. Results: The variables that showing the significant differences between two plots were pH water and KCl, soil OM, total C and HA yield. The insignificant differences were bulk density, total N, C/N ratio, E4/E6, phenol, carboxyl, total acidity and stable C. Conclusions: There is no significant difference between clear cut and TPSF in terms of carbon storage although TPSF had higher HA.